High-thermal-conductivity aluminum alloy material for 5G communication and preparation method thereof
By using nano-silicon and aluminum ingot materials in cast aluminum alloys, combined with the synergistic effects of Al-Sr and Al-Ca deteriorating agents and metal powders, the thermal conductivity of aluminum alloys is improved, and the thermal conductivity of existing aluminum alloys is solved. The problem of this solution meets the high thermal conductivity requirements of electronic communication equipment in complex structures.
Patent Information
- Application Number
- CN202411301283.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The thermal conductivity of existing cast aluminum alloys is less than 150W/(m·k), making it difficult to meet the heat dissipation needs of electronic communication products for complex structures and uneven wall thickness.
Using nano-silicon and aluminum ingot materials to heat up, add Al-Sr and Al-Ca as the degreasing agent, pass argon to degass, add copper powder, manganese powder, iron powder and magnesium powder, add nano seed crystals for refining, and finally Strontium powder is added and cast to prepare a highly thermally conductive aluminum alloy material.
By changing the stack sorting of silicon atoms and adding metal powder, the thermal conductivity of the alloy is significantly improved, meeting the high thermal conductivity of 5G communication equipment.
Smart Images

Figure BDA0005047743720000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of transfer films and relates to a high thermal conductivity aluminum alloy material for 5G communication and a preparation method thereof. Background Art
[0002] With the rapid development of electronic information, communication and other industries, electronic communication products such as base stations, inverters and radiators are gradually developing in the direction of high integration, miniaturization and lightweight, and the requirements for material heat dissipation performance are getting higher and higher. Therefore, high thermal conductivity materials have become the key to improving the heat dissipation capacity of equipment and reducing system temperature. Aluminum alloys have excellent thermal conductivity and processability, and also have the advantages of low cost and low density, so they can have high heat dissipation capacity while ensuring the lightweight of equipment. However, for products with complex structures and uneven wall thickness in the fields of electronics and communications, cast aluminum alloys are usually required. The silicon in cast aluminum alloys can improve the fluidity of the alloy, but as the silicon content increases, the thermal conductivity of the alloy decreases. This is mainly because the solid solubility of silicon in the α-Al matrix increases, aggravating the degree of lattice distortion, and as the silicon content further increases, the number of eutectic silicon in the organization increases and the size becomes coarse, which leads to increased free electron scattering, thereby reducing electrical conductivity and thermal conductivity. However, the thermal conductivity of common cast aluminum alloys is generally lower than 150W / (m·k), which is difficult to meet the requirements of components for heat dissipation. Summary of the invention
[0003] The present invention relates to a high thermal conductivity aluminum alloy material for 5G communication and a preparation method thereof, and belongs to the technical field of aluminum alloy materials. The present invention discloses a preparation method of a high thermal conductivity aluminum alloy material, which includes the following steps: (1) heating nano silicon and aluminum ingot materials and mixing them, and then adding a modifier for modification; (2) introducing argon gas for degassing, heating the materials by heating, adding copper powder, manganese powder and iron powder for mixing; (3) then adding magnesium powder for melting, adding nano crystal seeds for refining; (4) then keeping the temperature, adding strontium powder, mixing and casting to obtain a high thermal conductivity aluminum alloy material for 5G communication. The present invention uses Al-Sr and Al-Ca as modifiers, which are adsorbed on the growth steps of the silicon phase surface, preventing the adsorption of silicon atoms and poisoning the silicon phase growth surface, while changing the stacking order of silicon atoms so that the crystal grows in the same direction; in addition, adding metal powder further improves the high thermal conductivity of the alloy.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a high thermal conductivity aluminum alloy material for 5G communication, the method for preparing the high thermal conductivity aluminum alloy material comprising the following steps:
[0006] (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them;
[0007] (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing;
[0008] (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining;
[0009] (4) Then, the temperature is kept high, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
[0010] Furthermore, in the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 10-13:80-90:0.03-0.06, wherein the modifier is composed of Al-Sr and Al-Ca in a mass ratio of 1:1.
[0011] Furthermore, the heating in step (1) refers to heating to 850-900°C.
[0012] Furthermore, in the step (2), the degassing temperature and time are 750-780°C and 10-15 min respectively, and the heating temperature is 830-850°C.
[0013] Furthermore, in the step (2), the mass ratio of nano-silicon to copper powder is 100:0.2-0.6, and the mass ratio of copper powder, manganese powder and iron powder is 0.1-0.3:0.05-0.1:3.5-6.8.
[0014] Furthermore, in the step (3), the mass ratio of magnesium powder to copper powder is 0.1-0.5:3.5-8.2, and the mass ratio of magnesium powder to nano-seed crystals is 1:1-5, wherein the nano-seed crystals are Al3BC seed crystal alloys.
[0015] Furthermore, the specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 1-5:100.
[0016] Furthermore, the insulation temperature and time in step (4) are 750-770° C. and 5-10 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:1-5.
[0017] Beneficial effects of the present invention:
[0018] 1. The present invention uses Al-Sr and Al-Ca as modifiers, which are adsorbed on the growth steps on the surface of the silicon phase to prevent the adsorption of silicon atoms and the poisoning of the silicon phase growth surface, and at the same time change the stacking order of silicon atoms so that the crystals grow in the same direction; in addition, metal powders, namely copper powder, manganese powder and iron powder are added, and the three synergistically further improve the high thermal performance of the alloy. DETAILED DESCRIPTION
[0019] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.
[0020] Example 1
[0021] A method for preparing a high thermal conductivity aluminum alloy material for 5G communication, the method for preparing the high thermal conductivity aluminum alloy material comprising the following steps:
[0022] (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them;
[0023] (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing;
[0024] (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining;
[0025] (4) Then, the temperature is kept high, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
[0026] In the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 10:80:0.03, wherein the modifier is composed of Al-Sr and Al-Ca in a mass ratio of 1:1.
[0027] In step (1), the heating refers to heating to 850°C.
[0028] The degassing temperature and time in step (2) are 750° C. and 10 min respectively, and the heating temperature is 830° C.
[0029] In the step (2), the mass ratio of nano silicon to copper powder is 100:0.2, and the mass ratio of copper powder, manganese powder and iron powder is 0.1:0.05:3.5.
[0030] In the step (3), the mass ratio of magnesium powder to copper powder is 0.1:3.5, and the mass ratio of magnesium powder to nanocrystalline seeds is 1:1, wherein the nanocrystalline seeds are Al3BC seed alloy.
[0031] The specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 1:100.
[0032] The insulation temperature and time in step (4) are 750° C. and 5 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:1.
[0033] The nano silicon was purchased from: Huaxiang-llb87941221, the aluminum ingot material was purchased from: Baoquan-BQ2301039, the Al-Sr was purchased from: Hejifeng-AlSr10, Al-Ca was purchased from Rand, Al3BC seed alloy was purchased from Longxing, the refining agent was purchased from: Ganghuapai-SM30.
[0034] Example 2
[0035] A method for preparing a high thermal conductivity aluminum alloy material for 5G communication, the method for preparing the high thermal conductivity aluminum alloy material comprising the following steps:
[0036] (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them;
[0037] (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing;
[0038] (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining;
[0039] (4) Then, the temperature is kept high, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
[0040] In the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 11.5:85:0.04, wherein the modifier is composed of Al-Sr and Al-Ca in a mass ratio of 1:1.
[0041] In the step (1), the heating is to 875°C.
[0042] The degassing temperature and time in step (2) are 765° C. and 13 min respectively, and the heating temperature is 840° C.
[0043] In the step (2), the mass ratio of nano silicon to copper powder is 100:0.4, and the mass ratio of copper powder, manganese powder and iron powder is 0.2:0.08:4.8.
[0044] In the step (3), the mass ratio of magnesium powder to copper powder is 0.3:6, and the mass ratio of magnesium powder to nano-crystal seeds is 1:3.5, wherein the nano-crystal seeds are Al3BC seed alloy.
[0045] The specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 3.5:100.
[0046] The insulation temperature and time in step (4) are 760° C. and 7.5 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:2.5.
[0047] The nano silicon was purchased from: Huaxiang-llb87941221, the aluminum ingot material was purchased from: Baoquan-BQ2301039, the Al-Sr was purchased from: Hejifeng-AlSr10, Al-Ca was purchased from Rand, Al3BC seed alloy was purchased from Longxing, the refining agent was purchased from: Ganghuapai-SM30.
[0048] Example 3
[0049] A method for preparing a high thermal conductivity aluminum alloy material for 5G communication, the method for preparing the high thermal conductivity aluminum alloy material comprising the following steps:
[0050] (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them;
[0051] (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing;
[0052] (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining;
[0053] (4) Then, the temperature is kept high, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
[0054] In the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 13:90:0.06, wherein the modifier is composed of Al-Sr and Al-Ca in a mass ratio of 1:1.
[0055] In the step (1), the heating is to 900°C.
[0056] The degassing temperature and time in step (2) are 780° C. and 15 min respectively, and the heating temperature is 850° C.
[0057] In the step (2), the mass ratio of nano-silicon to copper powder is 100:0.6, and the mass ratio of copper powder, manganese powder and iron powder is 0.3:0.1:6.8.
[0058] In the step (3), the mass ratio of magnesium powder to copper powder is 0.5:8.2, and the mass ratio of magnesium powder to nano-crystal seeds is 1:5, wherein the nano-crystal seeds are Al3BC seed alloy.
[0059] The specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 5:100.
[0060] The insulation temperature and time in step (4) are 770° C. and 10 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:5.
[0061] The nano silicon was purchased from: Huaxiang-llb87941221, the aluminum ingot material was purchased from: Baoquan-BQ2301039, the Al-Sr was purchased from: Hejifeng-AlSr10, Al-Ca was purchased from Rand, Al3BC seed alloy was purchased from Longxing, the refining agent was purchased from: Ganghuapai-SM30.
[0062] Comparative Example 1
[0063] On the basis of Example 2, a method for preparing a high thermal conductivity aluminum alloy material for 5G communication is provided, and the method for preparing the high thermal conductivity aluminum alloy material comprises the following steps:
[0064] (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them;
[0065] (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing;
[0066] (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining;
[0067] (4) Then, the temperature is kept high, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
[0068] In the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 11.5:85:0.04, wherein the modifier is Al-Sr.
[0069] In the step (1), the heating is to 875°C.
[0070] The degassing temperature and time in step (2) are 765° C. and 13 min respectively, and the heating temperature is 840° C.
[0071] In the step (2), the mass ratio of nano silicon to copper powder is 100:0.4, and the mass ratio of copper powder, manganese powder and iron powder is 0.2:0.08:4.8.
[0072] In the step (3), the mass ratio of magnesium powder to copper powder is 0.3:6, and the mass ratio of magnesium powder to nano-crystal seeds is 1:3.5, wherein the nano-crystal seeds are Al3BC seed alloy.
[0073] The specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 3.5:100.
[0074] The insulation temperature and time in step (4) are 760° C. and 7.5 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:2.5.
[0075] The purchase source of the nano silicon is: Huaxiang-llb87941221, the purchase source of the aluminum ingot material is: Baoquan-BQ2301039, the purchase source of Al-Sr is: Hejifeng-AlSr10, and the purchase source of the refining agent is: Ganghuapai-SM30.
[0076] Comparative Example 2
[0077] On the basis of Example 2, a method for preparing a high thermal conductivity aluminum alloy material for 5G communication is provided, and the method for preparing the high thermal conductivity aluminum alloy material comprises the following steps:
[0078] (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them;
[0079] (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing;
[0080] (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining;
[0081] (4) Then, the temperature is kept high, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
[0082] In the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 11.5:85:0.04, wherein the modifier is Al-Ca.
[0083] In the step (1), the heating is to 875°C.
[0084] The degassing temperature and time in step (2) are 765° C. and 13 min respectively, and the heating temperature is 840° C.
[0085] In the step (2), the mass ratio of nano silicon to copper powder is 100:0.4, and the mass ratio of copper powder, manganese powder and iron powder is 0.2:0.08:4.8.
[0086] In the step (3), the mass ratio of magnesium powder to copper powder is 0.3:6, and the mass ratio of magnesium powder to nano-crystal seeds is 1:3.5, wherein the nano-crystal seeds are Al3BC seed alloy.
[0087] The specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 3.5:100.
[0088] The insulation temperature and time in step (4) are 760° C. and 7.5 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:2.5.
[0089] The nano silicon was purchased from: Huaxiang-llb87941221, the aluminum ingot material was purchased from: Baoquan-BQ2301039, Al-Ca was purchased from Rand, Al3BC seed alloy was purchased from Longxing, and the refining agent was purchased from: Ganghuapai-SM30.
[0090] Comparative Example 3
[0091] On the basis of Example 2, the copper powder in step (2) was removed and replaced with manganese powder of equal mass, and the other conditions were consistent with Example 2.
[0092] Comparative Example 4
[0093] On the basis of Example 2, the manganese powder in step (2) was removed and replaced with copper powder of equal mass, and the other conditions were consistent with Example 2.
[0094] Comparative Example 5
[0095] On the basis of Example 2, the iron powder in step (2) was removed and replaced with an equal mass of manganese powder, and the other conditions were consistent with Example 2.
[0096] 1. Performance Testing
[0097] The high thermal conductivity aluminum alloys prepared in Example 2 and Comparative Examples 1-5 were made into block samples with a specification of 20 mm×20 mm×30 mm. The thermal conductivity of the samples was measured by an LFA-500 laser flash spectrometer. The test results are shown in Table 1.
[0098] Table 1 Test results
[0099]
[0100]
[0101] It can be seen from Table 1 that the thermal conductivity of Example 2 is greater than that of Comparative Examples 1-5, among which the addition of a single-component modifier in Comparative Examples 1-2 has the greatest impact on the thermal conductivity, and Comparative Examples 3-5 lack one of the copper powder, manganese powder and iron powder, and their thermal conductivity decreases.
[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high thermal conductivity aluminum alloy material for 5G communication, characterized in that: The preparation method of the high thermal conductivity aluminum alloy material comprises the following steps: (1) heating the nano-silicon and aluminum ingot materials and mixing them, and then adding a modifier and mixing them; (2) introducing argon gas for degassing, heating, adding copper powder, manganese powder and iron powder and mixing; (3) then adding magnesium powder to melt, adding nanocrystalline seeds and refining; (4) Then, the mixture is kept warm, strontium powder is added, and the mixture is cast to obtain a high thermal conductivity aluminum alloy material for 5G communication.
2. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: In the step (1), the mass ratio of nano-silicon, aluminum ingot material and modifier is 10-13:80-90:0.03-0.06, wherein the modifier is composed of Al-Sr and Al-Ca in a mass ratio of 1:
1.
3. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: The heating in step (1) refers to heating to 850-900°C.
4. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: The degassing temperature and time in step (2) are 750-780°C and 10-15 min respectively, and the heating temperature is 830-850°C.
5. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: In the step (2), the mass ratio of nano-silicon to copper powder is 100:0.2-0.6, and the mass ratio of copper powder, manganese powder and iron powder is 0.1-0.3:0.05-0.1:3.5-6.
8.
6. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: In the step (3), the mass ratio of magnesium powder to copper powder is 0.1-0.5:3.5-8.2, and the mass ratio of magnesium powder to nanocrystalline seeds is 1:1-5, wherein the nanocrystalline seeds are Al3BC seed alloy.
7. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: The specific steps of refining in step (3) are: mixing the refining agent with liquid nitrogen, spraying it into the metal liquid through a hydraulic tank, and allowing the metal solution to stand after the spraying, wherein the mass ratio of the refining agent to the liquid nitrogen is 1-5:
100.
8. The method for preparing a high thermal conductivity aluminum alloy material for 5G communication according to claim 1, characterized in that: The insulation temperature and time in step (4) are 750-770° C. and 5-10 min respectively, and the mass ratio of the strontium powder to the copper powder is 0.01:1-5.
Citation Information
Patent Citations
Aluminum-silicon alloy alterant and preparation and using methods thereof
CN107964614A
Preparation method of aluminum alloy material
CN108866366A
Preparation method of high-thermal-conductivity aluminum alloy material and high-thermal-conductivity die-cast aluminum alloy
CN108866397A
Preparation method for high-strength and high-thermal-conductivity die-casting aluminum alloy material and die-casting aluminum alloy material
CN110951979A
